An assessment of client service charter implementation in local authorities in Tanzania: A case of Tabora municipal council - Kanunu, Deusdedith C. (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for award of the degree of Master of Human Resource Management (MSc-HRM) of Mzumbe University